1990
DOI: 10.1159/000107137
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acetyl-<i>L</i>-Carnitine on Serum Levels of Cortisol and Adrenocorticotropic Hormone and Its Clinical Effect in Patients with Senile Dementia of Alzheimer Type

Abstract: Eleven patients with senile dementia of Alzheimer type were treated with acetyl-L-carnitine (ALC) intravenously for 10 days and then orally for 50 days. Serum levels of cortisol and adrenocorticotropic hormone were measured at baseline and after the intravenous treatment. Neuropsychological assessment was also carried out at the same times and at the end of the oral treatment. The results show a trend toward a decrease of the mean cortisol levels and a significant improvement of cognitive performances. These d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…This result was coincided with Laboni et al, (1987) who reported that Lcarnitine deficiency may play a major role in Na-K pump dysfunction in uremic patients. There was significant decrease in serum cortisol with L-carnitine injection which is agreed with Parnetti et al (1990).…”
Section: Discussionsupporting
confidence: 84%
“…This result was coincided with Laboni et al, (1987) who reported that Lcarnitine deficiency may play a major role in Na-K pump dysfunction in uremic patients. There was significant decrease in serum cortisol with L-carnitine injection which is agreed with Parnetti et al (1990).…”
Section: Discussionsupporting
confidence: 84%
“…ST200 was chosen as the reference drug since consistent evidence exists about its efficacy in improving cognitive functions in SDAT (Calvani & Carta 1991;Cucinotta et al 1988;Parnetti et al 1990;Rai et al 1990). …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ALC has been shown to promote acetylcholine synthesis and induce choline acetyltransferase activity (Imperato et al, 1989). ALC has been shown to be of some benefit in the treatment of AD (Carta & Calvani, 1991;Parnetti et al, 1990;Sano et al, 1992;Spagnoli et al, 1991). Spagnoli and colleagues conducted a randomized, double-blind, placebo-controlled trial, much as described in the present study.…”
mentioning
confidence: 99%